Β2‐Adrenoreceptor Agonists, Montelukast, and Parkinson Disease Risk. Issue 5 (23rd March 2023) - Liu, Bojing; Svenningsson, Per; Ludvigsson, Jonas F.; Lundholm, Cecilia; Wallin, Johan; Larsson, Henrik; Sjölander, Arvid; Williams, Dylan M.; Pedersen, Nancy L.; Wirdefeldt, Karin
Abstract : Objective: This study was undertaken to examine the association between montelukast use, β2‐adrenoreceptor (β2AR) agonist use, and later Parkinson disease (PD). Methods: We ascertained use of β2AR agonists (430, 885 individuals) and montelukast (23, 315 individuals) from July 1, 2005 to June 30, 2007, and followed 5, 186, 886 PD‐free individuals from July 1, 2007 to December 31, 2013 for incident PD diagnosis. We estimated hazard ratios and 95% confidence intervals using Cox regressions. Results: We observed 16, 383 PD cases during on average 6.1 years of follow‐up. Overall, use of β2AR agonists and montelukast were not related to PD incidence. A 38% lower PD incidence was noted among high‐dose montelukast users when restricted to PD registered as the primary diagnosis. Interpretation: Overall, our data do not support inverse associations between β2AR agonists, montelukast, and PD. The prospect of lower PD incidence with high‐dose montelukast exposure warrants further investigation, especially with adjustment for high‐quality data on smoking. ANN NEUROL 2023;93:1023–1028